DETERMINATION OF POTENTIAL BIOACTIVE COMPOUNDS AND THEIR ANTIOXIDANT ACTIVITIES OF SELECTED UNDERUTILISED LEGUMES - James, Samaila; Nwabueze, Titus Ugochukwu; Ndife, Joel; Onwuka, Gregory I.; Anuonye, Julian Chukwuemeka; Nwokocha, Lilian; Muhammad, Saba (FUDMA Journal of Sciences, 2026)
Indigenous underutilised legumes are important sources of bioactive compounds with potential to improve food and nutrition security, yet data on their phytochemical constituents remain limited. This study evaluated the bioactive profile, fibre fractions, and antioxidant properties of selected legumes, namely Treculia africana, Vigna subterranea, Phaseolus vulgaris, Cajanus cajan, Vigna unguiculata, Sphenostylis stenocarpa, Pentaclethra macrophylla, and Arachis hypogaea. Standard analytical methods were used to determine fibre components, antioxidant activity, and bioactive compounds. The results showed significant (p < 0.05) differences in fibre fractions among the samples. Hemicellulose, raffinose, cellulose, lignin, and stachyose varied across the legumes, with Pentaclethra macrophylla recording the highest hemicellulose content (17.18%), while Vigna subterranea had the lowest (12.15%). Higher levels of raffinose and related oligosaccharides were also observed in Pentaclethra macrophylla and Arachis hypogaea. Gas chromatography–mass spectrometry analysis identified a wide range of bioactive compounds associated with antioxidant and antimicrobial activities. Germination for three days significantly (p < 0.05) increased antioxidant capacity in all samples, with improvements ranging from 14.56% to 53.58%. The highest increase was recorded in Vigna unguiculata (53.5`8%), while Arachis hypogaea showed the least change (14.56%). However, in reducing power, Phaseolus vulgaris (57.14%) and Vigna unguiculata (57.25%) had the highest values at the end of 3-day germination. The findings indicate that these legumes are rich in functional compounds and respond positively to short-term germination, supporting their potential use in functional food development.
Keywords: Indigenous legumes; fibre fractions; bioactive compounds; antioxidant capacity